An N-heterocyclic carbene-palladium-η3-allyl chloride complex for the Suzuki-Miyaura coupling of aryl halides - Broekemier, Noland William; Broekemier, Noah Curtis; Short, Randall Thomas; Palencia, Hector (European Journal of Chemistry, 2014)
An unsymmetrical, well-defined N-heterocyclic carbene-palladium-η3-allyl chloride complex has been synthesized and used as an efficient catalyst for the Suzuki-Miyaura cross-coupling of aryl bromides and activated aryl chlorides. The catalyst provides moderate to high yields of cross-coupling products at 50 °C in 2 hours, using 1 mol % of the catalyst and isopropyl alcohol as solvent.